Association between serum uric acid and arterial stiffness in a large‐aged 40–70 years old population. Issue 7 (24th June 2022) - Vallée, Alexandre
Abstract: Arterial stiffness (AS), measured by arterial stiffness index (ASI), is a determinant in cardiovascular (CV) diseases. A high serum uric acid (SUA) level is a known risk factor for CV disease. The authors investigated the relationship between SUA and ASI in the middle‐age UK Biobank population study. AS was defined as ASI > 10 m/s. A cross‐sectional study was conducted from 126 663 participants. Participants were divided into four quartiles according to SUA levels and sex. Sex multivariate analyses were performed with adjustment for confounding factors. The average ASI for overall participants was 9.3 m/s (SD: 2.9); 9.9 m/s (SD: 2.8) for men and 8.7 m/s (SD: 2.9) for women ( P < .001). Men presented higher SUA rate (351.3 mmol/L (SD:67.9)) than women (270.7 mmol/L (SD:64.4)), P < .001. In men multivariate analysis, SUA remained a determinant of AS, with an increase in the strength of the association between the quartiles, Q4 versus Q1, OR = 1.10 [1.05–1.16], P < .001, Q3 versus Q1, OR = 1.09 [1.04–1.14], P < .001 but not between Q2 and Q1 ( P = .136). In women, SUA remained significant for AS, with an increase in the strength of the association between the quartiles, Q4 versus Q1, OR = 1.22 [1.15–1.30], P < .001, Q3 versus Q1, OR = 1.13 [1.07–1.19], P < .001 and no difference between Q2 and Q1 ( P = .101). When applying continuous SUA values in the multivariate analysis, SUA remained significant ( P < .001), with a Youden index value for men = 338.3 mmol/L and for women = 267.3 mmol/L. High SUA levels were associated with AS, suggesting that SUA could be used as a predictor of atherosclerosis.